Tata Kelola Intelijen: Netralitas BIN dalam Politik Kepentingan - Wibowo, karyono; Dzikrullah, Akhlish; Julianto, Nico (Jurnal Kajian Stratejik Ketahanan Nasional, 2024)
A conflict of interest in the context of decision making is the potential for interference with a person's ability to make correct decisions on behalf of others. The study illustrates that a conflict of interest can threaten the independence of the Indonesian State Intelligence Agency (BIN) in carrying out its duties of early detection and early warning of national security threats. By detailing the current situation, including President Jokowi's announcement regarding his access to intelligence information, the article highlights potential conflicts of interest that could harm BIN's independence. In order to maintain BIN's integrity and independence, this case study emphasizes the need to evaluate recent changes in regulations, as well as efforts to minimize political content in intelligence agency decisions and operations. In conclusion, the article underlines that wise and transparent handling of conflicts of interest is the key to maintaining BIN's integrity and credibility in supporting Indonesia's national security In this research, information has been collected from various literature sources that have conducted investigations on relevant research topics. Using scientific sources obtained from Google Scholar searches and relevant books, this research investigates national defense and security in the cyber era, as well as national defense governance. The conclusion of this research is that conflicts of interest can threaten democracy and the integrity of intelligence institutions.